ANALISIS FINANCIAL PERFORMANCE TERHADAP NILAI PERUSAHAAN DIMODERASI DENGAN KEBIJAKAN DIVIDEN: Bahasa Indonesia - Jaunanda, Meiliana; Cunny, Ivana (Ultimaccounting Jurnal Ilmu Akuntansi, 2021)
Abstract - This study discusses to insight investors and companies on how to assess the company's prospects for the longterm in terms of section liquidity, profitability, leverage and dividend policy on firm value.. The financial ratios used in the study include Current Ratio, Return on Assets, and Debt to Equity Ratio. Firm value is proxied by Tobin's Q, and the moderating variable, namely Dividend Policy, is proxied by Dividend Payout Ratio. This research uses manufacturing companies that distribute positive dividends listed on the IDX during the 2017-2019 period and data obtained from S&P Capital IQ. There are 58 companies sampled in the study. The results obtained are (a) CR has no significant effect on Tobin's Q because the significant value is 0.206, (b) ROA and DER have a significant effect on Tobin's Q because the significance value of ROA and DER is 0.000, (c) DPR can moderate the relationship between CR and Tobin's Q because the significant value of DPR*CUR is 0.001, (d) DPR cannot moderate the relationship between ROA and Tobin's Q because the significant value of DPR*ROA is 0.351, (e) DPR can moderate the relationship between DER and Tobin's Q because the significant value of DPR*DER is 0.006. Keywords: Current Ratio; Debt to Equity Ratio; Dividend Payout Ratio; Firm Value; Return on Asset,